2011
DOI: 10.1007/s11325-011-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in patients with large pleural effusion: impact of thoracentesis

Abstract: Patients with large pleural effusion have poor subjective and objective sleep quality that improves after thoracentesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Only one published study has examined the effect of pleural effusion on sleep [35 ▪ ] and found poor sleep quality and efficiency in patients ( n  = 19) with a large pleural effusion at baseline as measured by the Pittsburgh Sleep Quality Index and overnight sleep studies.…”
Section: Pathophysiological Effects Of a Pleural Effusionmentioning
confidence: 99%
“…Only one published study has examined the effect of pleural effusion on sleep [35 ▪ ] and found poor sleep quality and efficiency in patients ( n  = 19) with a large pleural effusion at baseline as measured by the Pittsburgh Sleep Quality Index and overnight sleep studies.…”
Section: Pathophysiological Effects Of a Pleural Effusionmentioning
confidence: 99%
“…This is quite important, as pleural effusions can have a large impact on dyspnea, quality of life, sleep, and exercise. 4,6,52,53 Table 2 summarizes the most recent studies on the physiologic impact of thoracentesis. The physiologic basis for improvements is likely multifactorial.…”
Section: Understanding the Physiologic Impact Of Thoracentesismentioning
confidence: 99%
“…1 Therapeutic thoracentesis is associated with improvements in oxygenation, 2 pulmonary mechanics, gas exchange, 3 spirometry, the 6-minute walk test, 4 and sleep. 5 The management of pleural disease has recently undergone a paradigms shif,t whereby patient-centered outcomes, including hospital readmissions, morbidity, and mortality, are paramount. Although the availability of biochemical data in pleural effusions allows physicians to fine-tune individualized patient management, future effusion analysis may allow us to predict outcomes.…”
Section: Introductionmentioning
confidence: 99%